PEMANFAATAN MODIFIED AUTHENTICATED KEY AGREEMENT PROTOCOL WITH TIME STAMP PADA APLIKASI SECURE INSTANT MESSAGING - Binsar Mangisi Tobing, Deny; Setiyo Sukarno, Aji (Proceedings of KNASTIK, 2012)
Instant messaging (IM) a service that is used as a communication medium has severaladvantages since we can communicate in real-time, fast, and with very low cost. Theseadvantages led to the growing number of IM users of the service both from business,military, and government. However, since security aspects were not a design prioritythe emergence of threats such as eavesdropping and replay attacks also increased inrecent years. Therefore,additional security measures are required to prevent the threat.Secure Instant Messaging (SIM) is a software that implements the technique IMencryption, key agreement and authentication with the aim of preventing eavesdroppingand replay attacks. SIM the encryption of the message before it is transmitted overcommunication channels. Based on the results of testing, the process of authentication,encryption and decryption do not degrade performance significantly based on time andmemory used. Key agreement requires an average time of 25-32 seconds. This causesconsiderable delay occurred in the SIM application. On memory testing, key agreementrequires a 56% memory.